Experimental study on fire behaviors in narrow bifurcated channel with a confined portal. Issue 13 (3rd October 2021) - Chen, Changkun; Zhang, Yulun; Lei, Peng; Zeng, Wenqi; Jiao, Weibing
ABSTRACT: A series of experiments were conducted in a bifurcated channel consisting of horizontal main and branch channels to investigate the effects of branch and the confined ratio (the ratio of confined area to cross-section area at branch portal) on fire behaviors. The cross-angle between main and branch channels was 45° and ethanol pool fire fixed in the main channel center was used as fire source. Temperature distribution and flame behavior inside channel were recorded and analyzed. The results show that the branch leads to a much difference in the pattern of smoke flow and makes flame tilt to proximal sidewall to some extent, which is probably ascribed to the asymmetrical air entrainment in spatial. Cold air entrained through branch channel and downstream of main channel is more tend to carry hot smoke into upstream to enhance heat exchange and disturbance to smoke layer, which causes temperature field to asymmetrically distribute and high-temperature region to migrate to upstream. The confined ratio, which determines the proportion of opening area at branch portal, has no obvious influence on temperature distribution of main channel, while it could significantly affect temperature distribution inside the branch channel. The temperature below branch channel ceiling significantly increases with the increase of confined ratio at branch portal, and a corresponding empirical equation is developed. Additionally, under current experimental conditions, the maximum ceiling temperature in bifurcated channel is obviously lower than that of ordinary channel and decreases as confined ratio increases.